Pharmacokinetics and brain penetration of carbapenems in mice. Issue 5 (May 2016) - Matsumoto, Kazuaki; Kurihara, Yuji; Kuroda, Yuko; Hori, Seiji; Kizu, Junko
Abstract: An adverse effect associated with the administration of carbapenems is central nervous system (CNS) toxicity, with higher brain concentrations of carbapenems being linked to an increased risk of seizures. However, the pharmacokinetics and brain penetration of carbapenems have not yet been examined. Thus, the aim of this in vivo investigation was to determine the pharmacokinetics and brain penetration of carbapenems in mice. Blood samples and brain tissue samples were obtained 10, 20, 30, 60, and 120 min after the subcutaneous administration of carbapenems (91 mg/kg). We obtained the following values for the pharmacokinetic parameters of carbapenems in mice: 1.20–1.71 L/h/kg for CLtotal /F, 1.41–2.03 h −1 for Ke, 0.34–0.51 h for T1/2, 0.66–0.95 L/kg for Vss /F, 0.49–0.73 h for MRT, 83.46–110.58 μg/mL for Cmax, plasma, and 0.28–0.83 μg/g for Cmax, brain tissue . The AUC0−∞ of the carbapenems tested in plasma were in the following order: doripenem > meropenem > biapenem > imipenem, and in brain tissue were: imipenem > doripenem > meropenem > biapenem. The degrees of brain tissue penetration, defined as the AUC0−∞, brain tissue / f AUC0−∞, plasma ratio, were 0.016 for imipenem, 0.004 for meropenem, 0.002 for biapenem, and 0.008 for doripenem. The results of the present study demonstrated that, of the carbapenems examined, imipenem penetrated brain tissue to the greatest extent.